Time-Course of Prednisone Effects on Hormonal and Inflammatory Responses at Rest and During Resistance Exercise - Collomp, K.; Zorgati, H.; Cottin, F.; Do, M.-C.; Labsy, Z.; Gagey, O.; Lasne, F.; Prieur, F.; Collomp, R. (Hormone and Metabolic Research, 2015)
Glucocorticoids are among the most commonly used drugs. They are widely administered for acute and chronic musculoskeletal pain, as well as for several other pain syndromes, although their therapeutic use is sometimes diverted for doping purposes. Their time-course effects on hormonal and inflammatory responses nevertheless remain poorly understood, both at rest and during exercise. We therefore studied the alterations induced by 1 week of prednisone treatment (60 mg daily) in recreationally trained male athletes after 2 days (i. e., acute) and 7 days (i. e., short-term). Hormonal (i. e., DHEA, DHEA-S, aldosterone, and testosterone) and pro- and anti-inflammatory markers (i. e., IL-6, IL-10, and IL-1β) were investigated at rest and after resistance exercise. A significant decrease in DHEA and DHEA-S (p<0.01) without change in the DHEA/DHEA-S ratio, aldosterone, or testosterone was demonstrated after acute prednisone intake. A significant increment in IL-10 and a significant decrement in IL-6 (p<0.05) were also observed with prednisone both at rest and during exercise, without significant change in IL-1β. Continued prednisone treatment led to another significant decrease in both DHEA and DHEA-S (p<0.05), whereas no change in the inflammatory markers was observed between days 2 and 7. Our data demonstrate that the anti-inflammatory effects of prednisone were maximal and stable from the beginning of treatment, both in rest and exercise conditions. However, hormonal concentrations continued to decline during short-term intake. Further studies are needed to determine the effects of hormonal time-course alterations with longer glucocorticoid treatment and the clinical consequences.
Keywords: glucocorticoid; resistance exercise; kinetic; DHEA-S; aldosterone; cytokines